The mediating role of positive psychological capital in the relationship between acculturative stress and ethnic identity among ethnic minority university students in Mainland China - Yao, Shujing; Mohd Khir, Azlina; Ma’rof, Aini Azeqa; Wan Jaafar, Wan Munira (Human Resource Management Academic Research Society, 2023)
Previous research indicates that there exists a link between ethnic identity, acculturative stress, and psychological capital. Since there are own ethnic identities and Chinese national identities among Chinese ethnic groups. The present study aims to examine the relationship among these variables, specifically in the context of ethnic minority university students. Additionally, this study investigates the potential mediating role of positive psychological capital. To assess ethnic identity, positive psychological capital, and acculturative stress, three scales were employed, and structural equation modeling was utilized to explore the associations and potential pathways between these variables. The sample comprised 533 ethnic minority university students, aged 17-23, from two universities located in Hunan. The findings reveal that ethnic minority university students possess a strong sense of ethnic identity, with their Chinese national identity significantly surpassing their ethnic identity. Furthermore, a significant negative correlation is observed between Chinese national identity and acculturative stress. Both Chinese national identity and own ethnic identity demonstrate a significant positive correlation with positive psychological capital. Structural equation modeling indicates that positive psychological capital partially mediates the relationship between ethnic identity and acculturative stress. These findings underscore the significance of ethnic identity and positive psychological capital in mitigating acculturative stress among ethnic minority university students.